Removal of high-concentration geosmin using a GAC filter and a cross-flow-type membrane filtration process combined with PAC. Issue 2 (8th January 2016) - Choi, Jungsu; Lee, Dongho; Lee, Kihee; Joo, Hyunjong
Abstract: The purpose of this study is to remove high-concentration geosmin (GSM) by applying a granular-activated carbon (GAC) filter and a membrane filtration (MF) process injected with powdered-activated carbon (PAC). In this study, laboratory-scale experiments were conducted to (1) develop isotherm equations for GSM adsorption using PAC and GAC, (2) assess GSM adsorption competition by dissolved organic carbon (DOC), and (3) derive design factors for a pilot plant. In addition, the flux of the cross-flow-type pressurized MF was assessed at various PAC concentrations. Based on the results, a pilot plant was designed and operated from 14 July to 16 August 2013. The pilot plant operation achieved not only a stable treated water quality with an average GSM concentration of 10 ng/L or less (removal efficiency: 99.5%), but also a treated water quality with an average DOC concentration of 0.5 mg/L or less (removal efficiency: 91.7%) at the same time. From these findings, it was concluded that it may be possible (a) to meet the monitoring criteria for drinking water quality when high-concentration GSM is exposed, (b) to reduce the total amount of PAC inputs, and (c) to redress possible public complaints about compounds with unpleasant taste and odor.